Impacts of the “Coal to Gas” Policy on Rural Air VOC Level and Ozone Potentials in North China - Zhiyong Li; Chen Liu; Chengjing Cao; Zhen Zhai; Changtao Huang; Zhuangzhuang Ren; Jixiang Liu; Lan Chen; Songtao Guo; Dingyuan Yang (Aerosol and Air Quality Research)
Abstract A unique study was enacted during the heating season (HS) in 2020 and 2021 at a rural site in the Beijing-Tianjin-Hebei region to evaluate the policy impacts of “Coal to Gas” (CTG) on ambient volatile organic compounds (VOCs). A total of 58 VOCs in air and flue gas from wall-mounted gas stoves (WMGS) were concurrently analyzed. The total VOCs decreased from 38.6 µg m−3 in 2020 to 32.8 µg m−3 in 2021, indicating the CTG played a positive role. However, the ozone formation potentials (OFPs) increased from 31.5 to 44.9 µg m−3. Toluene, vinylidene chloride, ethylbenzene, o, m, p-xylene, 4-methyl-2-pentanone, n-butylbenzene, trans-1,2-dichloroethylene, and 1,2,4-trimethylbenzene were the main contributors to the OFPs. Halohydrocarbons contributed the most to ∑58VOCs of 54.8% and 54.4% in 2020 and 2021, respectively. It should be noted that the sustained CTG made WMGS the largest VOC source, replacing coal combustion (CC) in 2020. The CC contributions decreased from 33.2% in 2020 to 28.7% in 2021, while the WMGS far increased from 22.5% to 35.6%. Potential source contribution function (PSCF) modelling showed that the WMGS originated mainly from local emissions. High VOCs appeared surprisingly in clean days, because the WMGS and advanced coal-burning stoves with low particle emission prevailed in heating modes. The recognition of WMGS was achieved by coefficients of correlation and divergence between the positive matrix factorization (PMF) identified factor and field measured profiles of WMGS. This study firstly evidenced that the use of WMGS was becoming a major VOC source in rural north China. Meanwhile, the coal combustion for heating was still serious in rural area despite the “Coal Prohibition” law. The study was expected to provide some novel strategies for further VOC control and air quality improvement in rural area.